Oxytocin injection quality in Ethiopia: a post-marketing surveillance study in public and private facilities across three regions - Pete Lambert; Tri-H Nguyen; Victoria L Oliver; Andrew J L McArthur; Cleo Goodall; Alula M Teklu; Bikila Bayissa; Zelalem Mamo; Delayehu Bekele; Michelle P McIntosh (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background The high prevalence of poor quality essential medicines in low and middle income countries (LMIC) presents considerable risks in terms of both health outcomes and economic cost. Oxytocin injection, the gold standard therapy for management of postpartum haemorrhage (PPH), presents a particular challenge in this area. Recent studies in India, Nigeria and DRC have identified product failure rates, in terms of low drug content, to be 41%, 74% and 80% respectively. Ethiopia bears a high burden of PPH with over 40% of maternal deaths being directly attributed to haemorrhagic causes. This study assessed the quality of oxytocin injection at points in the public and private supply chains to support national efforts to address PPH in Ethiopia. # Methods This study sampled oxytocin injection ampoules from 45 sites across Oromia, Afar regions and the administrative area of Addis Ababa. This included points along the public supply chain from the national point of entry for supplies through regional hubs to points of use (public and private facilities) in urban and rural areas. Collected samples were stored under refrigerated conditions until analysis for oxytocin content, known degradation products and microbiological quality. # Results Ninety-six percent of ampoules passed all tests, while two samples (4%) contained less than the specified oxytocin content. Both samples were collected from rural facilities in Afar, a remote, poorly resourced region with a very hot climate. All supplies collected were sourced from European stringent regulatory approved (SRA) suppliers and, where storage conditions could be determined, approximately 95% of samples were stored in the refrigerator at the time of collection. # Conclusions The study indicates that oxytocin injection in the selected regions is generally of high quality and being stored appropriately. The failed samples detected in Afar suggest challenges remain around maintenance of refrigerated storage in least resourced settings. These findings contrast with recent results in other African countries and support the joint World Health Organization (WHO)/United Nations Children Fund/United Nations Population Fund statement that the availability of high quality oxytocin injection at the point of use is dependent on procurement of supplies from manufacturers approved by WHO or SRAs and storage at 2-8°C throughout the supply chain.